IMPLEMENTATION OF DIABETES DIET EDUCATION AND FOOT EXERCISE TO INCREASE KNOWLEDGE LEVEL AND REDUCE BLOOD SUGAR LEVELS IN DIABETES MELLITUS PATIENTS IN THE TLOGOSARI PUSKESMAS AREA, KULON SEMARANG - Ns. Novita Wulan Sari; Nur Sholiha Rositayani (International Journal Of Health Science, 2021)
Diabetes mellitus is pancreas disorder which can't produce any insulin as needed body. Diabetes diet education and legs exercise are one of combination non pharmacology theraphy which safe for increase knowledge level and decrease blood sugar level in diabetes mellitus sufferer. This study’s aim is to determine the description of the applicaton of diabetes diet education and legs exercise toward knowledge level and blood sugar level in diabetes mellitus sufferer trough a family nursing care approach. This type of research is descriptive with a case study approach. Subject used a number of 2 people with criteria age 40-75 years old, can verbal communication, don't have any physical disorder, and GDS is between 160-240 mg/dL. Knowledge level and GDS measurement using questionnaire sheet and glukometer. Diabetes diet education for 1 day and legs exercise intervention for 3 consecutived days. The results of data analysis showed that subject I experienced a increase in knowledge level score from 12 (enough) to 18 (good) and decrease in blood sugar level from 208 mg/dL (high) to 191 mg/dL (high), subject II experienced a increase in knowledge level score from 9 (less) to 16 (good) and decrease in blood sugar level from 182 mg/dL (high) to 169 mg/dL (high). The result of this case study concluded that there were increase of knowledge level and decrease of blood sugar level in diabetes sufferer. Diabetes diet education and legs exercise are reccomended as nursing intervention in diabetes management because they are able to increase knowledge level and decrease blood sugar level significantly and easily applied.